Reviving Romania's Growth and Convergence Challenges and Opportunities : A Country Economic Memorandum - World Bank (Washington, DC, 2013)
This Country Economic Memorandum (CEM) sets a framework for a dialogue on inclusive economic growth and income convergence in Romania. Generous Foreign Direct Investment (FDI) and other financial inflows lifted consumer demand, built up key industries, modernized wholesale trade and unleashed the movement of labor from low-productivity activities like agriculture towards high-productivity activities like manufacturing. Public and private investments in education lifted tertiary education enrollment from 12 to 23 percent. Preliminary calculations suggest that this growth was shared even after the crisis, as the income of the bottom 40 percent of the population grew by 5.5 percent on average during the 2000-2011 periods, a pace slightly above the 4.8 percent growth in the income of all households and the 4.1 percent average growth. Achievements notwithstanding, there is little room for complacency. The report discusses the immediate constraints to economic growth in areas where the short-term pay-off is high rather than covering all potential sources of growth for Romania. Although these are only the initial steps to reignite growth, the challenges of addressing each of these constraints should not be underestimated. Tackling them effectively demands a strong strategic vision, meticulous planning, and policy coordination. A significant amount of strategic communication of the benefits of the outlined reforms for the country will also be required since the roadblock to shaping and implementing these policies is likely to be vested interests, institutional inertia and lack of political consensus. In short, the crisis revealed the weakness of Romania's past growth model: it was based to a large extent on consumption and short-term capital inflows rather than on sustained productivity increases in tradable sectors and it concealed significant inefficiencies in the public sector.